Growth and yield response of cucumber (Cucumis sativus L.) To administering bokashi fertilizer and cow manure - Haria, Fransiska Roslina; Harahap, Rahmaniah; Harahap, Lutfi Henderlan (Contributions of Central Research Institute for Agriculture, 2024)
This research was carried out in the experimental field of the Faculty of Agriculture, Indonesian Community Development University (UPMI), Medan. Jalan Waqf, Pasar 12, Marindal 2, Patumbak District, Deli Serdang Regency, at a height of 40 m above sea level in May–July 2023. The experimental design used in this research was a factorial randomized group design (RAK) consisting of two factors. namely Factor I: Provision of Bokasi Fertilizer (B), which consists of 3 levels, namely: B0 = 0 (control), B1 = 4 tons/ha (8 kg/plot), and B2 = 6 tons/ha (12 kg/plot). Factor II: Provision of Cow Manure (K), which consists of 3 levels, namely: K0 = 0 kg/plot; 0 gr/plant; K1 = 2.5 kg/plot; 416.6 gr/plant, K2 = 3.5 kg/plot ; 583, 3 gr/plant. The parameters observed were plant height (cm), number of fruits per sample plant (fruit), fruit weight per sample plant (g), and stem diameter (mm). The results of the study showed that the single effect of giving cow manure had a significant effect on plant height at the age of 2 WAP and the number of fruit in the second harvest, but had no significant effect on plant height at the age of 1 WAP, 3 WAP, number of fruit in the I harvest, III harvest, weight. fruit in harvests I, II, and III, as well as fruit diameter in harvests I, II, and III; The single effect of giving cow manure had a significant effect on plant height at the age of 2 WAP and the number of fruit at harvest II, but had no significant effect on plant height at age 1 WAP, 3 WAP, number of fruit at harvest I, harvest III, weight of fruit at harvest. I, II, and III, as well as fruit diameter at harvest I, II, and III; The interaction effect of giving bokashi fertilizer and cow manure on the growth and development of cucumber plants had a significant effect on plant height at 2 days after planting, number of fruit at harvest II, and fruit weight at harvest II, but had no significant effect on plant height at 1 day after planting. 3 WAP, number of fruit in harvests I and III, fruit weight in harvests I and III, and fruit diameter in harvests I, II, and III.